2018
DOI: 10.3899/jrheum.171486
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Validation of the Digital Ulcer Clinical Assessment Score in Systemic Sclerosis

Abstract: Objective.To date, “healed/non-healed” and clinical judgment are the only available assessment tools for digital ulcers (DU) in patients with systemic sclerosis (SSc). The aim of our study is to examine a preliminary composite DU clinical assessment score (DUCAS) for SSc for face, content, and construct validity.Methods.Patients with SSc presenting at least 1 finger DU were enrolled and assessed with the Health Assessment Questionnaire–Disability Index, Cochin scale, visual analog scale (VAS) for DU-related pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 19 publications
0
23
0
Order By: Relevance
“…The HDISS-DU could be used in parallel with new clinical outcome measures currently in development, such as the DU clinical assessment score (DUCAS) for SSc [29]. The DUCAS is an objective, physician-defined measure that provides a composite clinical score for SSc-DUs; it was not developed with any patient input [29].…”
Section: Discussionmentioning
confidence: 99%
“…The HDISS-DU could be used in parallel with new clinical outcome measures currently in development, such as the DU clinical assessment score (DUCAS) for SSc [29]. The DUCAS is an objective, physician-defined measure that provides a composite clinical score for SSc-DUs; it was not developed with any patient input [29].…”
Section: Discussionmentioning
confidence: 99%
“…To address this need, in this issue of The Journal, Bruni, et al present the Digital Ulcer Clinical Assessment Score (DUCAS) in systemic sclerosis 10 . This outcome measure, designed for use in therapeutic trials, is the first composite measure developed to clinically assess DU.…”
Section: Gaining the Upper Hand On Systemic Sclerosis Digital Ulcersmentioning
confidence: 99%
“…This outcome measure, designed for use in therapeutic trials, is the first composite measure developed to clinically assess DU. Using consensus methodology, drawing upon the knowledge and experience of 8 experts in SSc-associated DU, the authors identified 7 domains important in the assessment of the burden of DU (Bruni, et al, Table 1) 10 . The final score is weighted across all 7 domains, with the weighting of each item determined by expert consensus, to give a total possible score of 19.5.…”
Section: Gaining the Upper Hand On Systemic Sclerosis Digital Ulcersmentioning
confidence: 99%
See 2 more Smart Citations